EFEKTIFITAS PAPARAN SINAR UV DAN ALKOHOL 70% TERHADAP TOTAL BAKTERI PADA UANG KERTAS YANG BEREDAR DI MASA PANDEMI COVID-19 - Elisanti, Alinea Dwi; Ardianto, Efri Tri; Ida, Novita Cholifah; Hendriatno, Eryk (Jurnal Riset Kefarmasian Indonesia, 2020)
Corona virus disease (COVID-19) has become a global pandemic in the world. Indonesia has declared this pandemic as a national disaster. Positive cases and deaths have increased every day. This was a long list of the effects of the COVID-19 pandemic on life. Several solutions have been designed to prevent the rapid transmission of this virus, one of them was by making sterilizer and hand sanitizer products. But there was still debate regarding the effectiveness of the use of UV rays and antiseptics as hygiene products offered.So we need a study to determine the effectiveness of UV exposure and the use of antiseptics to kill germs. This study used an experimental design, the sample used was in the form of folding money taken by the bacteria and grown on the media so that were classified into 3 groups, namely without treatment, 70% alcohol treatment and 10 seconds UV light treatment. The samples were analyzed using the dilution agar method and swab test with two repetitions. The results showed the average number of colony forming units (cfu) of bacteria using the dilution test method and swab test methode were 419 cfu on without treatment group; 4 cfu on alcohol 70% ; and 150 cfu on UV light (10 seconds). The alcohol 70% was more effective than 10 seconds UV light exposure to reduce the amount of bacterial cfu on folding money.